Anti-fertility effect of various plants at Dayak Tribe to Swiss Webster Mice - Agus Haryono; Yohanes Edy Gunawan; Suatma Suatma; Surisman Sumitro; Mohammad Rahmadu (Journal of Tropical Life Science, 2013)
Blumea balsamifera D.C, Croton tiglium L, Metroxylon sagu Rottb,and Fagraea racemosa Jackwere used as traditional anti-fertilty of Dayak people in Central Kalimantan. These study are to find out the potential plant as anti-fertility on Swiss Webster (SW) mice. Extracts of Blumea balsamifera D.C, Croton tiglium L, Metroxylon sagu Rottb andFagraea racemosa Jack were administered by gavage at the dose level of 0.26 mg/kg body weight (bw) to female of SW mice for 8 days to examined of estrous cycle.To determine of anti-fertility were administered by gavage of 0.26 mg/kg bw of plant extract to female SW mice and mated with normal male of SW mice. Estrous cycle were analyses every day for 9 days and reproduction display were examined at 15 days after fertilization. The result showed, that estrous cycle are inhibited on estrus and metestrus phase for all of extract traditional plant. Reproduction display showed decrease in the number of live fetuses, number of corpus luteum and body weight of the dam mice treated. The decrease in the corpus luteum further and fetuses attributes antifertilty effect of extract to inhibited foliculogenesis. Out of four extracts tested, Blumea balsamifera D.C extract seems to be more potent in anti-fertility activities compared with other extract of traditional plant. Keywords:Anti-fertility plants, Mus musculus